Analysis of the brazilian academic production regarding the topic “The biology textbook and biological evolution” (Revista Contexto & Educação, 2023)
This research characterized as a study of the “state of the art” type aimed to analyze the Brazilian academic production, expressed in the form of dissertations and theses, defended in the period from 2008 to 2018, which focused on the theme “Textbook of Biology and Biological Evolution”. We identified 7 documents that were collected in two online databases, the selection of which occurred through the reading of titles, abstracts and keywords, and were subsequently examined in their entirety. The results showed that the theme was little explored, especially with regard to doctoral and professional master’s research, and this reduced production was concentrated in the Southern region of Brazil, more specifically in the state of Rio Grande do Sul. We found that most of the objectives proposed by the researchers were to analyze the evolutionary content present in biology textbooks and/or their approach. Most of the results of these studies indicated deficiencies and limitations in the presentation of biological concepts/contents found in the investigated textbooks.
Keywords: Biology Textbook; Biological Evolution; State of the Art; Dissertations and Theses.